A pH-sensitive stearoyl-PEG-poly(methacryloyl sulfadimethoxine)-decorated liposome system for protein delivery: An application for bladder cancer treatment - Vila-Caballer, Marian; Codolo, Gaia; Munari, Fabio; Malfanti, Alessio; Fassan, Matteo; Rugge, Massimo; Balasso, Anna; de Bernard, Marina; Salmaso, Stefano (Journal of controlled release, 2016)
Stealth pH-responsive liposomes for the delivery of therapeutic proteins to the bladder epithelium were prepared using methoxy-poly(ethylene glycol)5kDa-1,2-distearoyl-sn-glycero-3-phosphoethanolamine (mPEG5kDa-DSPE) and stearoyl-poly(ethylene glycol)-poly(methacryloyl sulfadimethoxine) copolymer (stearoyl-PEG-polySDM), which possesses an apparent pKa of 7.2. Liposomes of 0.2:0.6:100, 0.5:1.5:100 and 1:3:100 mPEG5kDa-DSPE/stearoyl-PEG-polySDM/(soybean phosphatidylcholine+cholesterol) molar ratios were loaded with bovine serum albumin (BSA) as a protein model. The loading capacity was 1.3% w/w BSA/lipid. At pH7.4, all liposome formulations displayed a negative zeta-potential and were stable for several days. By pH decrease or addition to mouse urine, the zeta potential strongly decreased, and the liposomes underwent a rapid size increase and aggregation. Photon correlation spectroscopy (PCS) and transmission electron microscopy (TEM) analyses showed that the extent of the aggregation depended on the stearoyl-PEG-polySDM/lipid molar ratio. Cytofluorimetric analysis and confocal microscopy showed that at pH6.5, the incubation of MB49 mouse bladder cancer cells and macrophages with fluorescein isothiocyanate-labelled-BSA (FITC-BSA) loaded and N-(Lissamine Rhodamine B sulfonyl)-1, 2-dihexadecanoyl-sn-glycero-3-phosphoethanolamine triethylammonium salt (rhodamine-DHPE) labelled 1:3:100 mPEG5kDa-DSPE/stearoyl-PEG-polySDM/lipid molar ratio liposomes resulted in a time-dependent liposome association with the cells. At pH7.4, the association of BSA-loaded liposomes with the MB49 cells and macrophages was remarkably lower than at pH6.5. Confocal images of bladder sections revealed that 2h after the instillation, liposomes at pH7.4 and control non-responsive liposomes at pH7.4 or 6.5 did not associate nor delivered FITC-BSA to the bladder epithelium. On the contrary, the pH-responsive liposome formulation set at pH6.5 and soon administered to mice by bladder instillation showed that, 2h after administration, the pH-responsive liposomes efficiently delivered the loaded FITC-BSA to the bladder epithelium. [Display omitted]